Behavioural studies of the actions of cocaine, monoamine oxidase inhibitors and iminodibenzyl compounds on central dopamine neurones - Christie, Janice (1973)
Behavioural studies of the actions of cocaine, monoamine oxidase inhibitors and iminodibenzyl compounds on central dopamine neurones